Bronchial asthma: a global health problem - SNEHA SINGH,; RAKESH YADAV, (International Journal of Pharma and Bio Sciences, 2016)
Among the several diseases, asthma is categorized to be a chronic disorder or inflammatory ailment of the airways across the globe. Almost 18-20 million people in the United States and more than 250 million people worldwide are affected wit this syndrome. Numbers of patients are refractory to the available therapies. Newer agents are needed day by day to control symptoms and exacerbations in all patients. Over the years, there have been extensive advances in the understanding of asthma physiology at genetic level, airway biology, and immune cell signaling. Due to progression in the molecular level, diverse research groups have led to the development of number of molecules which may improve asthma care in the future. Several new classes of anti-asthma drugs—including ultra long acting β agonists, modulators of the interleukin pathways, adenosine receptor antagonist are named to be few. Some of the agents are in earlier phases of the development. Even though various groups have some preliminary efficacy data, there is insufficient confirmation to make strong recommendations about the use of these newer drugs. The mainstay of future research is on the clinical efficacy of newer agents, the effect of biological agents on severe asthma patients, and the understanding at cellular level of corticosteroid resistant asthma is needed to reduce the morbidity of asthma worldwide. The present review article is intended to give comprehensive information about the pathophysiology, pathogenesis and the medications for the management of asthma.